Gambaran Kelengkapan Administrasi Peserta Bukan Penerima Upah dengan Pembuatan Buku Saku Sebagai Pedoman Klaim - Dina Amalia; Agus Aan Adriansyah (Yayasan Literasi Sains Indonesia, 2023)
Based on article 15 paragraph 1 of the Law of the Republic of Indonesia Number 24 of 2011 requires all employers and their employees to register as participants in the social security protection program at BPJS Ketenagakerjaan. Registration for participants has an administrative flow starting from recording data such as personal information from participants. Based on the results of the Old Age Security report data at the BPJS Ketenagakerjaan Branch X office as of October 2022 there were 19,602 claims, with 536 cases canceled status, caused by a lack of files, and not meeting the criteria. This study aims to find out the description of participants' personal information from various segments at BPJS Ketenagakerjaan Branch X. This type of research was taken with a qualitative approach. The targets or participants of this study are employees in the field of membership and heads of HR and General Affairs at BPJS Ketenagakerjaan Branch X. Participants were taken using non-probability with a purposive sampling technique. This research was conducted during November 2022 – February 2023. The results showed that the pocket book was declared valid and could be used as a guideline for administrative completeness for Non-Wage Beneficiary participants at BPJS Ketenagakerjaan Branch X with an average total validation of 3.4.